2016
DOI: 10.3174/ajnr.a4675
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Structural Differentiation between Native Arteriogenesis and Therapeutic Synangiosis in Intracranial Arterial Steno-Occlusive Disease

Abstract: Background and Purpose Encephaloduroarteriosynangiosis has been shown to generate collateral vessels from the extracranial to the intracranial circulation in patients with moyamoya disease and intracranial arterial steno-occlusive disease. The mechanisms involved are not well understood. We hypothesize that angiogenesis is the leading mechanism forming collaterals after encephaloduroarteriosynangiosis as there are no preexisting connections, which should exhibit higher architectural complexity compared to nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Interestingly, a presumed hypoxia-driven type of NCF occurs in patients with pMCAO caused by steno-occlusive moyamoya disease or following indirect surgical revascularization to relieve chronic ischemia in the MCA territory. 54 – 58 Also of note, Marushima et al. 59 reported that indirect bypass surgery using implantation of the temporalis muscle with myoblasts expressing VEGFA improved outcome after pMCAO in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a presumed hypoxia-driven type of NCF occurs in patients with pMCAO caused by steno-occlusive moyamoya disease or following indirect surgical revascularization to relieve chronic ischemia in the MCA territory. 54 – 58 Also of note, Marushima et al. 59 reported that indirect bypass surgery using implantation of the temporalis muscle with myoblasts expressing VEGFA improved outcome after pMCAO in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a presumed hypoxia-driven type of NCF occurs in patients with pMCAO caused by steno-occlusive moyamoya disease or following indirect surgical revascularization to relieve chronic ischemia in the MCA territory. [54][55][56][57][58] Also of note, Marushima et al 59 reported that indirect bypass surgery using implantation of the temporalis muscle with myoblasts expressing VEGFA improved outcome after pMCAO in mice. Our finding that systemic hypoxia and pMCAO induce NCF is consistent with preliminary reports in adult mouse heart for systemic hypoxia 21,22 and following coronary artery ligation, 20 with the latter recently being confirmed in neonatal mice.…”
Section: Neo-collateral Formation Induced By Hypoxia and Mca Occlusionmentioning
confidence: 99%
“…The LCFD value equals 1.0 when the object is a one-dimensional straight line. LCFD equals 2.0 when the object is two-dimensional and completely covered 51 . Pixels in the 8 × 8 environment of the seed pixel are considered to be connected.…”
Section: Methodsmentioning
confidence: 99%
“…Arteriogenesis involves the recruitment and enlargement of pre-existing vessels, and sprouting and splitting are not parts of this process. A previous study showed that when a collateral develops into a vessel distal to a stenosis, higher flow and increased shear stress are associated with the enlargement of the collateral vessel ( 11 ). We found no significant difference in the CD34 bri CD133 + CD45 dim KDR + cell count among the three spontaneous collateral circulation groups, although the heterozygous c.14429G>A (p.R4810K) of RNF213 was significantly correlated with spontaneous collateral circulation.…”
Section: Discussionmentioning
confidence: 99%
“…The uncertainty of post-surgical synangiosis is the main consideration that limits the use of this method. According to earlier reports, collateral vessel formation in encephaloduroarteriosynangiosis (EDAS), a commonly used indirect revascularization surgery, may be primarily driven by angiogenesis ( 10 , 11 ). Angiogenesis is induced by hypoxia and involves the formation of new collateral vessels by sprouting or splitting from the pre-existing vascular structures ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%